A novel cationic emulsifier used for preparing slow-cracking and rapid-setting asphalt: Synthesis, surface activity, and emulsification ability. Issue 4 (3rd April 2018) - Wang, Yuexin; Gao, Yaqin; Zhang, Qian; Meng, Qing
ABSTRACT: A novel cationic emulsifier including nonionic fatty alcohol polyoxyethylene ether was synthesized in two steps from epichlorohydrin, octadecyl dimethyl amine, and fatty alcohol polyoxyethylene ether, and the intermediate product could also be used as an emulsifier. Their structures were characterized by FTIR, and the surface activities were investigated by surface tension, electrical conductivity, and HLB. The obtained results indicated that the critical micelle concentration (CMC) of the final product was low, 0.442 mmol/L, and the surface tension at the CMC was 41.02 mN/m. The hydrophile-lipophile balance (HLB) value was 12, which meet the requirements of asphalt emulsifiers. A series of experiments of the emulsified asphalt prepared by the emulsifiers were performed. The results showed that the emulsified asphalt could be stably stored for more than 5 days when the emulsifier was 2 wt% and the pH value was between 3 and 4. The result of demulsification experiments showed that the emulsifier is a slow-cracking and rapid-setting asphalt emulsifier. GRAPHICAL ABSTRACT: